Leveraging COBIT 2019 Framework for Recommending ERP System Module Development at Cardboard Manufacturing Industry - Dharmada, Tralya; Wiratama, Jansen; Faza, Ahmad (Asosiasi Doktor Sistem Informasi Indonesia, 2024)
The manufacturing industry is a cornerstone of Indonesia's economy, contributing significantly to the nation's GDP and exhibiting consistent growth. The sector's advancement is closely linked with technological innovations, particularly those associated with Industry 4.0, which integrates advanced technologies into production processes. Enterprise Resource Planning (ERP) systems play a pivotal role among these technologies. However, maximizing the potential of ERP systems necessitates robust IT governance, which can be assessed using the COBIT 2019 framework. This research targets the Cardboard Manufacturing Industry, which has not previously undergone an IT governance assessment, primarily due to the lack of a dedicated IT division. The study evaluates the current state of IT governance within the industry, focusing on specific objectives, including APO12 (Manage Risk), BAI09 (Manage Assets), APO14 (Manage Data), and EDM05 (Ensure Stakeholder Engagement). The methodology involves a comprehensive evaluation using the COBIT 2019 framework to identify gaps between the current and desired capability levels. The findings reveal significant discrepancies in IT governance maturity, highlighting improvement areas. Consequently, the study proposes recommendations to bridge these gaps, enhancing overall IT governance. Suggestions for developing customized ERP modules are further provided to support the industry's technological integration and efficiency.